EVALUASI KARBOHIDRAT DAN LEMAK BATANG TANAMAN PISANG (Musa paradisiaca. Val) HASIL FERMENTASI ANAEROB DENGAN SUPLEMENTASI NITROGEN DAN SULFUR SEBAGAI BAHAN PAKAN TERNAK - Dhalika, Tidi; Mansyur, -; Budiman, Atun (Pastura; Vol 2 No 2DO - 10.24843/Pastura.2013.v02.i02.p10)
The aim of this study was to evaluation of carbohydrate and extract ether consentration of anaerobic fermentation banana pseudostem with supplementation of nitrogen and sulfur as ruminants feed component. This study was arranged with an experimental research by Completely Randomized Design with 3 x 3 factorial. The first factor are supplementation of 0%, 1% and 2% nitrogen, and second factor are supplemetation of 0%, 0,04% and 0,08% sulphur, with 4 (four) times replication. The parameter of this research is the nutrition value, i,e ; crude fiber, nitrogen free extract and extract ether concentration. The result of this research showed that not interaction between supplemetation of nitrogen and sulphur on carbohydrate and extract ether consentration of anaerobic fermentation banana pseudostem, and suplementation of 2,00% nitrogen and 0,08% sulphur give influence on decreasing of crude fiber concentration, about 14,07%, and ether extract concentration, about 54,24%, but not alteration on nitrogen free extract in anaerobic fermentation banana pseudostem.
Keywords: banana pseudostem, nitrogen, sulphur and anaerobic fermentation.